Cellular transplant therapies for globoid cell leukodystrophy: Preclinical and clinical observations. Issue 11 (November 2016) - Maher, Keri R.; Yeager, Andrew M.
Abstract : Globoid cell leukodystrophy (GLD) is a progressive neurodegenerative disorder caused by the deficiency of galactocerebrosidase (GALC), resulting in accumulation of toxic metabolites in neural tissues. Clinically variable based on age of onset, infantile GLD is generally a rapidly fatal syndrome of progressive neurologic and cognitive decline, whereas later‐onset GLD has a more indolent, protracted clinical course. Animal models, particularly the twitcher mouse, have allowed investigation of both the pathophysiology of and the potential treatment modalities for GLD. Cellular therapy for GLD, notably hematopoietic cell transplantation (HCT; transplantation of bone marrow, peripheral blood stem cells, or umbilical cord blood cells) from a normal related or unrelated allogeneic donor provides a self‐renewing source of GALC in donor‐derived cells. The only currently available treatment option in human GLD, allogeneic HCT, can slow the progression of the disease and improve survival, especially when performed in presymptomatic infants. Because persistent neurologic dysfunction still occurs after HCT in GLD, preclinical studies are evaluating combinations of HCT with other treatment modalities. © 2016 Wiley Periodicals, Inc.